Meningkatkan Kemampuan Komunikasi Matematik Siswa SMP Dengan Pendekatan Contextual Teaching and Learning Melalui Model Cooperative Learning Tipe Numbered Head Together - Gina Aulia Rahman (Universitas Maritim AMNI Semarang, 2024)
This research aims to examine whether the achievement and improvement of junior high school students' mathematical communication skills who use the Contextual Teaching and Learning approach through the Numbered Head Together type Cooperative Learning model is better than those who use regular learning. The method used in this research is experimental. This research was conducted at one of the state junior high schools in Cianjur Regency with a population of all class VIII, while the sample was taken from two classes randomly where one class was the experimental class and the other class was the control class. This research instrument is about description. The research data were processed using the Microsoft Office Excel 2007 application and SPSS 16 software. Based on the research results, the author concluded that the achievement and improvement in mathematical communication skills of junior high school students whose learning used the Contextual Teaching and Learning approach through the Numbered Head Together type Cooperative Learning model was better than that using regular learning.